Conductometric determination of the two angiotensin-converting enzyme (ACE) inhibitors, Ramipril and Enalapril maleate in pure form and in tablets using phosphotungestic acid - Abdel-monem, AfafAboul-khier; Bahgat assaf, Eman Ahmed (Innovare Journal of Medical Sciences, 2018)
Simple and sensitive conductometric method has been developed for the determination of Ramipril and Enalapril maleate using phosphotungestic acid in pure form and in tablets. The proposed method Â is based on the conductometric determination of 5-20 mg and 7-20 mg of Ramipril and Enalapril maleate by titration with phosphotungstic acid (PTA) in aqueous solution. All the reaction conditions for the proposed methods have been studied. The proposed methods were applied successfully for the determination of Ramipril and Enalapril maleate Â in tablets, the RSD values were not exceeding 2 for both drugs. The results obtained were compared statistically with those obtained by the reference method and showed no significant differences regarding accuracy and precision.